2011
DOI: 10.1158/1055-9965.epi-11-0340
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofEGFRGenetic Variants on Glioma Risk and Patient Outcome

Abstract: Background: The epidermal growth factor receptor (EGFR) regulates important cellular processes and is frequently implicated in human tumors. Three EGFR polymorphisms have been described as having a transcriptional regulatory function: two single-nucleotide polymorphisms in the essential promoter region, À216G/T and À191C/A, and a polymorphic (CA) n microsatellite sequence in intron 1. We aimed to elucidate the roles of these EGFR polymorphisms in glioma susceptibility and prognosis.Methods: We conducted a case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 42 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…HOTAIR is a known oncogenic lncRNA in several tumor types (reviewed in [7,8]) including gliomas [15][16][17]. The roles of HOTAIR have been widely reported Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOTAIR is a known oncogenic lncRNA in several tumor types (reviewed in [7,8]) including gliomas [15][16][17]. The roles of HOTAIR have been widely reported Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other putative causes may include familial aggregation, genetic syndromes, telomere maintenance and genetic polymorphisms [12][13][14]. The importance of inherited genetic variants in glioma risk has been highly addressed in both candidate-gene and genomewide association studies (GWAS) approaches, which revealed single nucleotide polymorphisms (SNPs) in cancer-related genes associated with glioma risk (e.g., TERT, EGF, EGFR, TGF-β1, CCDC26, CDKN2A/CDKN2B, PHLDB1 and RTEL1 [15][16][17][18]). …”
Section: Introductionmentioning
confidence: 99%
“…EGFR is the main tyrosine kinase receptor expressed in gliomas, and a high level of expression is correlated with tumor malignancy and unfavorable prognosis [24,25]. The EGFR transactivation mechanism requires the cleavage and shedding of membrane-bound EGFR ligands by ADAM17 [12,13,26].…”
Section: Discussionmentioning
confidence: 99%
“…Also genetic differences concerning drug target can explain differences in response or toxicity between individuals. The number of cytosine/adenine repeats in the intron 1 of epidermal growth factor receptor (EGFR), can affect the receptor activity and could potentially interfere with the activity of EGFR inhibitors as cetuximab [7].…”
Section: Editorialmentioning
confidence: 99%
“…Impaired glucuronidation activity of the UGT1A1 enzyme is a predisposing factor to severe irinotecan toxicity, due to a genetic polymorphism of the UGT1A1 gene. UGT1A1*28 is a TA indel polymorphism characterized by an extra TA repeated in the promoter region of the gene [A(TA) 7 TAA]. This polymorphism is thought to be associated with reduced glucuronidation of SN38, the active metabolite of irinotecan, compared with wild-type UGT1A1 [A(TA) 6 TAA], leading to variability in the PK of SN38 [4].…”
Section: Editorialmentioning
confidence: 99%